High‐Quality Graphene Using Boudouard Reaction - Artem K. Grebenko; Dmitry V. Krasnikov; Anton V. Bubis; Vasily S. Stolyarov; Denis V. Vyalikh; Anna A. Makarova; Alexander Fedorov; Aisuluu Aitkulova; Alena A. Alekseeva; Evgeniia Gilshtein; Zakhar Bedran; Alexander N. Shmakov; et al. (Advanced Science, 2022)
Abstract Following the game‐changing high‐pressure CO (HiPco) process that established the first facile route toward large‐scale production of single‐walled carbon nanotubes, CO synthesis of cm‐sized graphene crystals of ultra‐high purity grown during tens of minutes is proposed. The Boudouard reaction serves for the first time to produce individual monolayer structures on the surface of a metal catalyst, thereby providing a chemical vapor deposition technique free from molecular and atomic hydrogen as well as vacuum conditions. This approach facilitates inhibition of the graphene nucleation from the CO/CO2 mixture and maintains a high growth rate of graphene seeds reaching large‐scale monocrystals. Unique features of the Boudouard reaction coupled with CO‐driven catalyst engineering ensure not only suppression of the second layer growth but also provide a simple and reliable technique for surface cleaning. Aside from being a novel carbon source, carbon monoxide ensures peculiar modification of catalyst and in general opens avenues for breakthrough graphene‐catalyst composite production.